Midnight sun - Speer, Scott, 1982-; Thorne, Bella, 1997-; Schwarzenegger, Patrick, 1993-; Riggle, Rob; Shephard, Quinn, 1995-; Tremblett, Ken, 1965-; Mathew, Suleka (Universal City, CA : Universal Pictures Home Entertainment, 2018)
17-year-old Katie Price has been sheltered since childhood with a rare disease that makes even the smallest amount of sunlight deadly. During the day she is housebound, but after nightfall, Katie can venture out to the local train station and play her guitar for travelers. One night, her dreams come true when she's noticed by Charlie, whom she has secretly admired for years, and decides to hide her condition from him as the two embark on a uniquely powerful romance over one nearly perfect summer.
Originally released as a motion picture in 2018.
Wide screen (2.40:1).
Special features: Midnight sun: An inside look.
Original score, Nathaniel Walcott ; costume designer, Jori Woodman ; production designer, Eric Fraser ; editor, Tim Nolan, Michelle Harrison ; director of photography, Karsten 'Crash' Gopinath.
Bella Thorne, Patrick Schwarzenegger, Rob Riggle, Quinn Shephard, Ken Tremblett, Suleka Matthew.
MPAA rating: PG-13; for some teen partying and sensuality.
Keywords: Romance films; Coming of age films